A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing and a preparation method thereof

By using graphene/carbon nanotube/silicon carbide ceramic matrix composite slurry in 3D printing, combining phenolic resin modification and reasonable proportion of powder particles, the problem of insufficient strength and toughness of silicon carbide ceramic materials is solved, and ceramics are realized The high density and mechanical properties of the material are improved.

CN117776727BActive Publication Date: 2024-12-27WEIHAI YUNYI INTELLIGENT TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311587272.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2024-12-27
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize graphene and carbon nanotubes in 3D printing to improve the strength and toughness and performance of silicon carbide ceramic materials, and the strength and toughness effect of traditional methods is limited.

Method used

Using graphene/carbon nanotube/silicon carbide ceramic-based composite slurry, the good flowability and shearing are prepared by reasonably proportioning powder particles and additives of different particle sizes, such as sodium alginate and polyethylene glycol 400. The shear-diluted slurry is combined with phenolic resin modified graphene and carbon nanotubes to achieve synergistic strength.

Benefits of technology

The compactness and mechanical properties of ceramic materials are significantly improved, including bending strength and fracture toughness, and the synergistic effects of graphene and carbon nanotubes significantly enhanced the mechanical properties of SiC matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117776727B_ABST
    Figure CN117776727B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of printing materials, and more particularly to a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing and a preparation method thereof. The composite material slurry of the present invention comprises 52.38-61.1 parts of silicon carbide powder, 5.238-6.1 parts of carbon black powder, 0.297-1.4 parts of graphene powder, 0.594-1.75 parts of carbon nanotube powder, 29.25-39 parts of solvent, 0.75-1 parts of binder, and 0.6-0.7 parts of dispersant by weight. The graphene / carbon nanotube / silicon carbide ceramic-based composite material 3D printing slurry provided by the present invention quantitatively adds powder particles, binder, dispersant and solvent, and the obtained slurry has the advantages of good dispersion effect of reinforcing phase without agglomeration, slurry satisfies shear thinning behavior, and excellent mechanical properties of prepared ceramic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of printing materials, and in particular relates to a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics have the advantages of low density, high specific strength, high specific modulus, high temperature resistance, wear resistance and corrosion resistance. In recent years, many scholars have tried to use additive manufacturing technology to prepare complex structure silicon carbide ceramics, but the poor performance of the material, especially the large brittleness, limits its practical application. Therefore, strengthening and toughening has become one of the core issues in the research of SiC ceramic additive manufacturing. The traditional strengthening and toughening method is to improve the performance of ceramic materials by adding toughening phases such as micron-sized particles, whiskers, and fibers to the ceramic matrix. The toughening mechanism mainly includes crack deflection, crack cross-linking, microcracks, etc. The above-mentioned "traditional" strengthening and toughening methods are used to improve its strength and fracture toughness, and its strengthening and toughening effect is also very limited.

[0003] In recent years, in order to combine the advantages of graphene and carbon nanotubes, graphene and carbon nanotubes have been used together in composite materials. The effect of using graphene in combination with carbon nanotubes is significantly better than that of single graphene or carbon nanotubes. Among them, the three-dimensional (3D) heterogeneous hybridization of two-dimensional graphene and one-dimensional carbon nanotubes is the most feasible method to prevent the aggregation of carbonaceous nanomaterials and introduce the synergistic effect between carbon nanotubes, which can fully inherit the advantages of graphene and carbon nanotubes in nanomaterials. However, how to apply graphene and carbon nanotubes to the 3D printing direct writing technology of silicon carbide ceramics and prepare direct writing slurry with excellent performance has become an urgent problem to be solved. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention proposes a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing and a preparation method thereof. The graphene / carbon nanotube / silicon carbide ceramic-based composite material 3D printing slurry provided by the present invention has the advantages of good reinforcement phase dispersion effect, no agglomeration, the slurry satisfies the shear thinning behavior, and the prepared ceramic material has excellent mechanical properties.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] First of all, one of the purposes of the present invention is to provide a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, which includes the following components by weight: 52.38-61.1 parts of silicon carbide powder, 5.238-6.1 parts of carbon black powder, 0.297-1.4 parts of graphene powder, 0.594-1.75 parts of carbon nanotube powder, 29.25-39 parts of solvent, 0.75-1 part of binder, and 0.6-0.7 part of dispersant.

[0007] Furthermore, in the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, the silicon carbide powder consists of powders with average particle sizes of 10 microns and 1 micron.

[0008] Furthermore, the mass ratio of the silicon carbide powder with an average particle size of 10 micrometers to the silicon carbide powder with an average particle size of 1 micrometer is 7:3.

[0009] Furthermore, the average particle size of the carbon black powder is 5 microns.

[0010] Furthermore, the graphene powder has a thickness of 1-10 nanometers and a particle size of 20-40 micrometers.

[0011] Furthermore, the carbon nanotube powder has an outer diameter of 8-15 nanometers and a length of 30-50 micrometers.

[0012] From the particle stacking principle, it can be known that when the ceramic slurry flows and deforms under the action of external force, there are certain stacking gaps between the powder particles that constitute the slurry, and the liquid phase located in these stacking gaps cannot actually play a role in flow, which is equivalent to increasing the volume of the immobile area of ​​the ceramic slurry, increasing the viscosity of the ceramic slurry, and reducing the fluidity of the ceramic slurry. By using powder particles of different particle sizes to match, the powder particles of large particle size are stacked to form stacking gaps, and the powder particles of small particle size are filled in the stacking gaps, the liquid phase part of the original immobile area can be released to the greatest extent, and the content of the mobile liquid phase can be increased. Therefore, a reasonable powder particle size ratio can reduce the viscosity of the ceramic slurry and improve the fluidity. When the particle size ratio of 10 microns to 1 micron in silicon carbide powder is 7:3, the viscosity of the slurry is the lowest.

[0013] Furthermore, in the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, the solvent is deionized water and the binder is sodium alginate. Sodium alginate is commonly used as a gel additive in biological and food manufacturing, which is non-toxic, tasteless and low in cost. Sodium alginate as a binder can improve the plasticity of the slurry and meet the self-support requirements of direct writing.

[0014] Furthermore, the dispersant is polyethylene glycol 400. Polyethylene glycol 400 is a typical nonionic surfactant. In its molecular structure, there are only ether groups (COC) and hydroxyl groups (-OH), which are easy to form hydrogen bonds with the hydrogen-oxygen bonds on the surface of SiC particles, thereby forming an adsorption film on the surface of SiC particles, producing a steric hindrance effect. The steric repulsion generated between the steric hindrance layers on the surface of each particle can prevent collision and sedimentation between particles, thereby achieving stable distribution of SiC particles in the liquid phase.

[0015] Secondly, the second object of the present invention is to provide a method for preparing a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, comprising the following steps:

[0016] Step 1: Mix the solvent and the binder, stir evenly, and let stand to prepare a binder solution;

[0017] Step 2: dissolving a phenolic resin in ethylene glycol to obtain a phenolic resin solution, uniformly mixing the phenolic resin solution with graphene powder, and then vacuum filtering, drying, and calcining to obtain phenolic resin-modified graphene;

[0018] Step 3: dissolving phenolic resin in ethylene glycol to obtain a phenolic resin solution, uniformly mixing the phenolic resin solution with carbon nanotube powder, and then vacuum filtering, drying, and calcining to obtain phenolic resin-modified carbon nanotubes;

[0019] Step 4: Mix the phenolic resin modified graphene powder, phenolic resin modified carbon nanotube powder, silicon carbide powder and carbon black powder in proportion, stir evenly to obtain a premixed powder;

[0020] Step 5: adding a dispersant to the premixed powder obtained in step 4, stirring and dispersing the mixture to obtain a dispersed powder;

[0021] Step 6: Add the binder solution prepared in step 1 to the dispersed powder obtained in step 5, stir thoroughly, and prepare a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry.

[0022] Furthermore, the standing time in step 1 is 10-24 hours. If the time is less than 10 hours, the sodium alginate is not completely dissolved. If the time exceeds 24 hours, sodium alginate is an organic macromolecular compound, which is chemically unstable and easily oxidized by oxygen in the environment to change color. When sodium alginate is exposed to air, the hydroxyl and carboxyl groups in its molecules will react with oxygen in the air to produce new compounds, thereby causing its color to change and affecting its bonding effect.

[0023] Furthermore, the mass ratio of phenolic resin to graphene in the phenolic resin-modified graphene in step 2 is (4-8):1.

[0024] Furthermore, the method of mixing, filtering and calcining in step 2 is as follows: graphene powder is added to the phenolic resin solution, ultrasonically oscillated for 1-2 hours, stirred at 60°C in a magnetic stirrer for 12-36 hours, and then vacuum filtered, and the mixture obtained after filtration is placed in a vacuum drying oven and dried at 60°C for 24-36 hours. After drying, the mixture is placed in a vacuum tube furnace, heated to 800°C at a heating rate of 3°C / min under a vacuum environment, and then cooled to room temperature with the furnace after keeping warm for 1 hour.

[0025] Furthermore, in the step three, the mass ratio of phenolic resin to carbon nanotubes in the phenolic resin-modified carbon nanotubes is (4-8):1.

[0026] Furthermore, the method of mixing, filtering and calcining in step three is as follows: carbon nanotube powder is added to the phenolic resin solution, ultrasonically oscillated for 1-2 hours, stirred at 60°C in a magnetic stirrer for 12-36 hours, and then vacuum filtered. The mixture obtained after filtration is placed in a vacuum drying oven and dried at 60°C for 24-36 hours. After drying, the mixture is placed in a vacuum tube furnace, heated to 800°C at a heating rate of 3°C / min under a vacuum environment, kept warm for 1 hour, and then cooled to room temperature with the furnace.

[0027] Furthermore, a third object of the present invention is to provide graphene / carbon nanotube / silicon carbide ceramics obtained from the above-mentioned graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing.

[0028] Beneficial Effects

[0029] The present invention discloses a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing provided by the present invention uses powder particles of different particle sizes to form stacking gaps by stacking large-size powder particles, and small-size powder particles are filled in the stacking gaps, which can release the liquid phase part of the original immobile area to the greatest extent and increase the mobile liquid phase content. Therefore, a reasonable powder particle size ratio can reduce the viscosity of the ceramic slurry and improve fluidity.

[0031] (2) The slurry of the present invention has shear thinning behavior and meets the requirements of direct writing.

[0032] (3) The graphene / carbon nanotubes in the reaction-sintered silicon carbide composite ceramic of the present invention serve as a synergistic strengthening phase, which can significantly improve the density of the ceramic material while inhibiting the growth of ceramic crystal grains, and can effectively strengthen the SiC matrix grain boundaries. In addition, the graphene and carbon nanotubes can play a role in mutual dispersion and protection, and the synergistic strengthening effect is significant. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the slurry viscosity of samples 4-8 in the present invention;

[0034] Figure 2 is the flexural strength of the molding materials prepared by samples 4-8 in the present invention;

[0035] Figure 3 is the fracture toughness of the molding materials prepared by samples 4-8 in the present invention;

[0036] Figure 4 is the bending strength of the molding materials prepared by samples 1, 2, 3, 6, 9, 10, and 11 of the present invention;

[0037] Figure 5 It is the fracture toughness of the molding materials prepared by samples 1, 2, 3, 6, 9, 10 and 11 in the present invention. DETAILED DESCRIPTION

[0038] Hereinafter, the present invention will be described in detail. Before describing, it should be understood that the terms used in this specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted according to the meaning and concept corresponding to the technical aspects of the present invention on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented here are only preferred examples for illustrative purposes and are not intended to limit the scope of the present invention, so that it should be understood that other equivalents or improvements can be obtained therefrom without departing from the spirit and scope of the present invention.

[0039] The following examples are only listed as examples of embodiments of the present invention and do not constitute any limitation to the present invention. It can be understood by those skilled in the art that modifications within the scope of the essence and concept of the present invention fall within the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products.

[0040] Example 1

[0041] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 1.4 parts of graphene powder, 0.7 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0042] The mass ratio of powders with different average particle sizes in the silicon carbide powder is 7:3, with d50=10 μm and d50=1 μm.

[0043] Carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400.

[0044] The above raw materials were prepared into slurry as follows:

[0045] Step 1: Mix the solvent and the binder, stir evenly, and let stand for 12 hours to prepare a binder solution;

[0046] Step 2: 60 g of the phenolic resin is dissolved in 30 g of ethylene glycol to obtain a phenolic resin solution, 90 g of the phenolic resin solution is mixed with 10 g of graphene powder, ultrasonically vibrated for 2 h, stirred in a magnetic stirrer at 60 ° C for 24 h, and the mixed solution is vacuum filtered. The mixture obtained after filtration is placed in a vacuum drying oven at 60 ° C for 24 h. After drying, it is placed in a vacuum tube furnace, heated to 800 ° C at a heating rate of 3 ° C / min under a vacuum environment, and then cooled to room temperature with the furnace after keeping warm for 1 h, to obtain phenolic resin modified graphene;

[0047] Step 3: dissolving 60 g of phenolic resin in 30 g of ethylene glycol to obtain a phenolic resin solution, mixing 90 g of the phenolic resin solution with 10 g of carbon nanotube powder, ultrasonically vibrating for 1 h, stirring at 60° C. for 24 h in a magnetic stirrer, vacuum filtering the mixed solution, placing the filtered mixture in a vacuum drying oven at 60° C. for 24 h, placing it in a vacuum tube furnace after drying, heating it to 800° C. at a heating rate of 3° C. / min under a vacuum environment, keeping it warm for 1 h, and then cooling it to room temperature with the furnace to obtain phenolic resin modified carbon nanotubes;

[0048] Step 4: Mix phenolic resin modified graphene powder, phenolic resin modified carbon nanotube powder, silicon carbide powder and carbon black powder according to proportion, stir evenly to obtain premixed powder;

[0049] Step 5: adding a dispersant to the premixed powder obtained in step 4, stirring and dispersing the mixture to obtain a dispersed powder;

[0050] Step 6: Add the binder solution prepared in step 1 to the dispersed powder obtained in step 5, stir thoroughly, and prepare a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry, which is recorded as sample 1.

[0051] Example 2

[0052] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 0.7 parts of graphene powder, 1.4 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0053] The mass ratio of powders with different average particle sizes in the silicon carbide powder is 7:3, with d50=10 μm and d50=1 μm.

[0054] Carbon black: d50 = 5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as Sample 2.

[0055] Example 3

[0056] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 0.35 parts of graphene powder, 1.75 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, 0.7 parts of dispersant; the powder particles are silicon carbide (d50 = 10 μm and d50 = 1 μm ratio of 7:3), carbon black (d50 = 5 μm), graphene (thickness 1-10 nanometers, particle size 20-40 microns), carbon nanotubes (outer diameter 8-15 nanometers, length 30-50 microns), the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are prepared into a slurry according to the method of Example 1, recorded as sample 3.

[0057] Comparative Example 1

[0058] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 63 parts of silicon carbide powder, 6.3 parts of carbon black powder, 0 parts of graphene powder, 0 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0059] The mass ratio of the powders with different average particle sizes in the silicon carbide powder: d50=10 μm and d50=1 μm is 9:1; carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 4.

[0060] Comparative Example 2

[0061] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 63 parts of silicon carbide powder, 6.3 parts of carbon black powder, 0 parts of graphene powder, 0 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0062] The mass ratio of the powders with different average particle sizes in the silicon carbide powder: d50=10 μm and d50=1 μm is 8:2; carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 5.

[0063] Comparative Example 3

[0064] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 63 parts of silicon carbide powder, 6.3 parts of carbon black powder, 0 parts of graphene powder, 0 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0065] The mass ratio of the powders with different average particle sizes in the silicon carbide powder: d50 = 10 μm and d50 = 1 μm is 7:3. Carbon black: d50 = 5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 6.

[0066] Comparative Example 4

[0067] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 63 parts of silicon carbide powder, 6.3 parts of carbon black powder, 0 parts of graphene powder, 0 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0068] The mass ratio of the powders with different average particle sizes in the silicon carbide powder: d50=10 μm and d50=1 μm is 6:4; carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 7.

[0069] Comparative Example 5

[0070] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 63 parts of silicon carbide powder, 6.3 parts of carbon black powder, 0 parts of graphene powder, 0 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0071] The mass ratio of the powders with different average particle sizes in the silicon carbide powder: d50=10 μm and d50=1 μm is 5:5; carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 8.

[0072] Comparative Example 6

[0073] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 2.1 parts of graphene powder, 0 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0074] The silicon carbide powder has different average particle sizes: the ratio of d50=10 μm to d50=1 μm is 7:3; carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 9.

[0075] Comparative Example 7

[0076] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 0 parts of graphene powder, 2.1 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0077] The silicon carbide powder has different average particle sizes: the ratio of d50=10 μm to d50=1 μm is 7:3; carbon black: d50=5 μm; graphene: thickness 1-10 nanometers, particle size 20-40 micrometers; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 micrometers; the solvent is deionized water; the binder is sodium alginate; the dispersant is polyethylene glycol 400. The above raw materials are used to prepare a slurry according to the method of Example 1, which is recorded as sample 10.

[0078] Comparative Example 8

[0079] A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, composed of the following components by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 0.7 parts of graphene powder, 1.4 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder, and 0.7 parts of dispersant;

[0080] The mass ratio of powders with different average particle sizes in the silicon carbide powder: d50=10μm and d50=1μm is 7:3; carbon black: d50=5μm; graphene: thickness 1-10 nanometers, particle size 20-40 microns; carbon nanotubes: outer diameter 8-15 nanometers, length 30-50 microns; the solvent is deionized water; the binder is sodium alginate; and the dispersant is polyethylene glycol 400.

[0081] The above raw materials were prepared into slurry as follows:

[0082] Step 1: Mix the solvent and the binder, stir evenly, and let stand for 12 hours to prepare a binder solution;

[0083] Step 2: Mix graphene powder, carbon nanotube powder, silicon carbide powder and carbon black powder in proportion, stir evenly to obtain a premixed powder;

[0084] Step 3: adding a dispersant to the premixed powder obtained in step 2, stirring and dispersing the mixture to obtain a dispersed powder;

[0085] Step 4: Add the binder solution prepared in step 1 to the dispersed powder obtained in step 3, stir thoroughly, and prepare a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry, which is recorded as sample 11.

[0086] The slurry viscosity test was performed on the above samples, and each sample was tested 5 times and the average value was taken. The test results are as follows Figure 1As shown in the figure, it can be seen that with the increase of small-size SiC particles, the viscosity of the ceramic slurry shows a trend of first decreasing and then increasing, and when the particle size ratio of large and small particles is 7:3 (sample 6), the viscosity of the ceramic slurry is the lowest. This is because when there are fewer small-sized SiC particles, large-sized particles account for the vast majority of the ceramic slurry system, forming more stacking gaps, the liquid sodium alginate solution is in the stacking gaps, and there are more liquid-phase immobile areas, so the overall viscosity of the ceramic slurry is higher at this time; with the increase of small-sized SiC particles, the small-sized particles gradually fill the gaps between the large-sized particles and release the sodium alginate solution originally stored therein, and the mobile liquid phase in the ceramic slurry system gradually increases, so the overall viscosity of the ceramic slurry continues to decrease; when the small-sized SiC particles increase to 30wt% of the whole powder, the gaps between the large-sized particles are completely filled with small-sized particles, forming a tightly stacked structure, releasing the sodium alginate solution to the maximum extent, and making the viscosity of the ceramic slurry reach the lowest point; when the small-sized SiC particles continue to increase to more than 30wt%, there are still small-sized particles left after filling the gaps formed by the large-sized particles, and the excess small-sized SiC particles form new stacking gaps, which increases the immobile areas of the liquid sodium alginate solution, so the viscosity of the ceramic slurry increases. In order to ensure the appropriate viscosity and fluidity of the ceramic slurry, the particle size ratio of large and small SiC particles was determined to be 7:3.

[0087] The samples were subjected to direct writing 3D printing by the method in the prior art. After printing, the products were dried, degummed and sintered to obtain molded products. The bending strength of the obtained products was tested, and the average bending strength of the five specimens was taken as the final bending strength of the specimens under this condition.

[0088] like Figure 2 As shown in the figure, in samples 4-8, it can be seen that with the increase of small-size silicon carbide particles, the bending strength shows a trend of first increasing and then decreasing. The reason may be that when there are fewer small-size silicon carbide particles, they can evenly fill the gaps formed by the accumulation of part of the large-size particles, accelerate the discharge of gas during sintering, reduce the generation of defects such as pores in the sintered specimens, promote the densification of ceramics, and thus improve the bending performance of ceramic specimens. The more small-size silicon carbide particles there are within a certain range, the more stacking gaps are filled, so the bending performance of the ceramic specimen shows an upward trend at this time; when the small-size silicon carbide particles account for 30wt% of the total silicon carbide particles (sample 6), the small-size silicon carbide particles completely fill the gaps formed by the accumulation of large-size silicon carbide particles. At this time, the number of pores in the ceramic specimen is the least, and the mechanical properties are the best. The bending strength at this time is 232.7MPa; when the content of small-size silicon carbide particles exceeds 30wt%, too many small-size silicon carbide particles will cause the particles to agglomerate and form new stacking gaps, resulting in an increase in the number of defects such as pores, which is not conducive to the densification of ceramics, thereby causing a decrease in the bending performance of ceramics.

[0089] like Figure 4 As shown in the figure, the bending strength of silicon carbide composite ceramics with different proportions of carbon nanotubes added in samples 1-3, 6, 9-11. It can be clearly observed from the data analysis that the bending strength is improved with the addition of G / CNT. Regardless of the addition ratio of graphene / carbon nanotubes, the experimental results clearly verify the positive role of G / CNT in enhancing the bending strength of SiC matrix. Among them, when the ratio of graphene / carbon nanotubes is 1:2 (sample 2), it shows excellent mechanical properties, and the bending strength reaches 347.4MPa, which is 45.2% higher than the bending strength of the single-phase SiC (sample 6) sample. The results clearly show that the synergistic reinforcement effect of graphene and carbon nanotubes can significantly improve the mechanical properties of the composite material. Graphene and carbon nanotubes disperse and protect each other, further improving the overall performance of the composite material. When graphene and carbon nanotubes are modified with phenolic resin and added to the matrix (sample 11), molten silicon may react with the carbon source during the reaction sintering process to release a large amount of heat, causing the graphene and carbon nanotubes to melt. At the same time, graphene and carbon nanotubes are carbon nanomaterials. If they are not coated and modified, they can easily react with molten silicon, destroying their original structure and properties and reducing the strengthening and toughening effects.

[0090] The fracture toughness test of the obtained product was carried out, and the average fracture toughness of 5 specimens was taken as the final fracture toughness of the specimen under this condition.

[0091] like Figure 3 As shown in the figure, in samples 4-8, it can be seen that with the increase of small-size silicon carbide particles, the fracture toughness shows a trend of first increasing and then decreasing. The reason may be due to the existence of grain bridging mechanism. From the manager bridging mechanism, it can be seen that within a certain range, the larger the grain size, the more obvious the toughening effect. Therefore, when the content of small-size silicon carbide decreases, with the increase of large-size silicon carbide, some large-size grains are pulled out or broken under critical conditions, which increases the overall fracture toughness of the ceramic specimen. When small-size particles account for 30wt% of the total powder (sample 6), the fracture toughness reaches a maximum value of 3.37MPa·m 1 / 2 However, when the number of large-sized grains exceeds the critical value, the fracture toughness of the ceramic specimen shows a downward trend. This may be because the anisotropy between the grains causes the grains to undergo thermal expansion, which leads to deformation of the specimen and the generation of microcracks. The presence of microcracks will aggravate the expansion of cracks, thereby reducing the fracture toughness of the specimen.

[0092] like Figure 5As shown in the figure, in samples 1-3, 6, 9-11, similar to the bending strength, the experimental results clearly verify the positive role of G / CNT in improving the fracture toughness of SiC matrix. Among them, sample 2 shows excellent mechanical properties with a fracture toughness of 4.78MPa·m 1 / 2 , which is 40.6% higher than that of the single-phase SiC (sample 6).

Claims

1. A graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing, characterized in that: The invention comprises the following components in parts by weight: 61.1 parts of silicon carbide powder, 6.1 parts of carbon black powder, 0.7 parts of graphene powder, 1.4 parts of carbon nanotube powder, 29.25 parts of solvent, 0.75 parts of binder and 0.7 parts of dispersant.

2. The graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 1, characterized in that: The silicon carbide powder is composed of silicon carbide powder with an average particle size of 10 microns and silicon carbide powder with an average particle size of 1 micron; the carbon black powder has an average particle size of 5 microns; the graphene powder has a thickness of 1-10 nanometers and a particle size of 20-40 microns; the carbon nanotube powder has an outer diameter of 8-15 nanometers and a length of 30-50 microns.

3. The graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 1, characterized in that: The mass ratio of the silicon carbide powder having an average particle size of 10 micrometers to the silicon carbide powder having an average particle size of 1 micrometer is 7:

3.

4. The graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 1, characterized in that: The solvent is deionized water; the binder is sodium alginate; and the dispersant is polyethylene glycol 400.

5. The method for preparing the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Mix the solvent and the binder, stir evenly, and let stand to prepare a binder solution; Step 2: dissolving a phenolic resin in ethylene glycol to obtain a phenolic resin solution, uniformly mixing the phenolic resin solution with graphene powder, and then vacuum filtering, drying, and calcining to obtain phenolic resin-modified graphene; Step 3: dissolving phenolic resin in ethylene glycol to obtain a phenolic resin solution, uniformly mixing the phenolic resin solution with carbon nanotube powder, and then vacuum filtering, drying, and calcining to obtain phenolic resin-modified carbon nanotubes; Step 4: Mix the phenolic resin modified graphene powder, phenolic resin modified carbon nanotube powder, silicon carbide powder and carbon black powder in proportion, stir evenly to obtain a premixed powder; Step 5: adding a dispersant to the premixed powder obtained in step 4, stirring and dispersing the mixture to obtain a dispersed powder; Step 6: Add the binder solution prepared in step 1 to the dispersed powder obtained in step 5, stir thoroughly, and prepare a graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry.

6. The method for preparing the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 5, characterized in that: The standing time in step 1 is 10-24 hours; The mass ratio of phenolic resin to graphene in the phenolic resin-modified graphene in step 2 is (4-8):

1.

7. The method for preparing the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 5, characterized in that: The method of mixing, filtering and calcining in step 2 is as follows: graphene powder is added to the phenolic resin solution, ultrasonically oscillated for 1-2 hours, stirred at 60°C in a magnetic stirrer for 12-36 hours, and then vacuum filtered. The mixture obtained after filtration is placed in a vacuum drying oven and dried at 60°C for 24-36 hours. After drying, the mixture is placed in a vacuum tube furnace, heated to 800°C at a heating rate of 3°C / min under a vacuum environment, kept warm for 1 hour, and then cooled to room temperature with the furnace.

8. The method for preparing the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 5, characterized in that: The mass ratio of phenolic resin to carbon nanotubes in the phenolic resin-modified carbon nanotubes in step three is (4-8):

1.

9. The method for preparing the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 5, characterized in that: The method of mixing, filtering and calcining in step 3 is as follows: adding carbon nanotube powder to phenolic resin solution, ultrasonically oscillating for 1-2 hours, stirring at 60°C in a magnetic stirrer for 12-36 hours, and then vacuum filtering, placing the filtered mixture in a vacuum drying oven and drying it at 60°C for 24-36 hours, and after drying, placing the mixture in a vacuum tube furnace, heating it to 800°C at a heating rate of 3°C / min under a vacuum environment, keeping it warm for 1 hour, and then cooling it to room temperature with the furnace.

10. Graphene / carbon nanotube / silicon carbide ceramics obtained from the graphene / carbon nanotube / silicon carbide ceramic-based composite material slurry for direct writing 3D printing according to claim 1.

Citation Information

Patent Citations

  • Method for preparation of silicon carbide slurry with nano-carbontube and graphene as carbon sources

    CN103833034A

  • Composite silicon carbide ceramic powder and preparation method of ceramic separating valve

    CN114014667A